Improving Short-Term Memory of School-Age Children through Brain Gym with the Chunking Technique Mnemonic Approach - Harmiardillah, Sylvi; Kusbiantoro, Dadang; Safitri , Della Ika Aulia (Pijar : Jurnal Penelitian Bidang Pendidikan dan Pembelajaran, 2025)
Improving Children's Short-Term Memory through Brain Gym with Mnemonic Approach Chunking Technique. This study aims to determine the effect of brain gym with a mnemonic method approach to chunking techniques on short-term memory in 3rd and 4th grade students. The study used a pre-experimental design with a one-group pretest-posttest approach. The research subjects were 68 respondents selected using simple random sampling. Data collection was carried out using a questionnaire which was analyzed using the Wilcoxon test. The results of the analysis showed an increase in the average short-term memory score from 7.01 to 10.14 after the intervention. The Wilcoxon test results showed a p value = 0.000 (p < 0.05), which means there is a significant difference between memory before and after the intervention. Brain gym with chunking technique mnemonic method approach combines a series of simple stimulation movements and a method of remembering numbers that are broken down into smaller chunks to facilitate memory. This method can be applied as one of the strategies in improving student memory, both in the educational environment and in nursing practice in the process of child growth and development and the process of educating elementary school children in implementing daily learning activities.